Physicochemical properties of a ternary system based on medium chain triglycerides/water/mixed nonionic sugar-based surfactants - Ismail, Zahariah; Kassim, Anuar; Suhaimi, Hamdan; Ahmad, Salmiah (Taylor and Francis Group, 2001)
Equal ratios of medium chainlength triglycerides and water were emulsified with 5% w/w of mixed nonionic surfactants with various hydrophilic-lipophilic balance (HLB) values. The HLB numbers ranged from 15 to 6.6. Emulsifiers with HLB numbers 15, 14.2, 13.3, and 12.5 produced low viscosity milk-like liquid, 11.6, 10.8, 10, and 9.1 produced cream, 8.3 and 7.4 produced paste like consistency, and 6.6 produced a coarse emulsion. The effects of HLB on stability, particle size, and rheological properties were studied. Emulsifiers with intermediate HLB numbers produced emulsions that are stable for 30 days at room temperature but a thin layer of oil on top of the emulsion was observed at 45°C. The thin oil layer can be redispersed with mild agitation without loss of stability. Emulsifiers with high and low HLB number (15, 14.2, 13.3, 6.6) produced emulsions that were unstable at both storage conditions. The stability of the emulsions correlate well with the particle size. The curve flow plot for most of the emulsions fit the Herschel Bulkley model. They exhibit a pseudoplastic type behavior. Emulsifiers with different HLB numbers also affect the shear stress at zero shear, τo, and the yield value, τ.